MARKETING STRATEGY FOR THE HOUSEHOLD CASSAVA CHIPS INDUSTRY IN KALOSI VILLAGE, ALLA DISTRICT, ENREKANG DISTRICT - Darmiati Dahar; Muh. Jabal Nur (Paser Institute Management and Busines, 2024)
The development of regional superior-based agro-industrial areas is regional development that creates a healthy climate, adds value to raw materials and creates employment opportunities. Agroindustry development will spur economic growth. The agro-industrial commodity is cassava. Cassava is not durable and has a low price, if managed well it can provide high added value. Cassava (Manihot esculenta) is an important source of carbohydrates. The food industry meets food needs and generates foreign exchange for the country. "AZA" cassava chips is a household scale agro-industry that processes cassava as cassava chips. The household business "AZA" was founded in 2017 and is located in Kalosi Village, Alla District, Enrekang Regency, South Sulawesi Province. This research was carried out deliberately using a purposive sampling method. Qualitative methods were used to find, describe and explain marketing strategies. The research data analysis method used in this research is research using descriptive analysis and SWOT analysis. Internal factors influence the formation of strengths and weaknesses (S and W), such as: decision making which has an impact on marketing, finance, operations, human resources, research and development, management information systems and corporate culture. Processing of “AZA” Cassava Chips in profitable situations. This indicates that the industry is strong and has the opportunity to be used. Recommendations and strategies used are progressive.